The measurement of responsivity of infrared photodetectors using a cavity blackbody - Li, Nong; Jiang, Dongwei; Wang, Guowei; Chen, Weiqiang; Zhou, Wenguang; Jiang, Junkai; Chang, Faran; Hao, Hongyue; Wu, Donghai; Xu, Yingqiang; Shen, Guiying; Xie, Hui; et al. (Journal of semiconductors, 2023)
For the measurement of responsivity of an infrared photodetector, the most-used radiation source is a blackbody. In such a measurement system, distance between the blackbody, the photodetector and the aperture diameter are two parameters that contribute most measurement errors. In this work, we describe the configuration of our responsivity measurement system in great detail and present a method to calibrate the distance and aperture diameter. The core of this calibration method is to transfer direct measurements of these two parameters into an extraction procedure by fitting the experiment data to the calculated results. The calibration method is proved experimentally with a commercially extended InGaAs detector at a wide range of blackbody temperature, aperture diameter and distance. Then proof procedures are further extended into a detector fabricated in our laboratory and consistent results were obtained.